The entitlement of the Bayt al-Mal to a muslim praepositus’ estates; an analysis on the right of a Muslim to bequeath without obtaining a consent from the Bayt al-Mal - Abdullah, Mohamad Asmadi (The Social Sciences Research Society, 2012)
The bayt al-mal or public treasury was established during the reign of Umar al- Khattab, the second rightly-guided Caliph. It originated during the Prophet Muhammad s.a.w. time but not as an institution. Its main function is to administer wealth contributed and acquired by Muslims through various sources. Under the Islamic law of succession, the bayt al-mal may constitute a recipient of a deceased Muslim’s estate. It would exhaust the estates after being allotted to quranic heirs, in the absence of any asabah. A question arises in what capacity the bayt al-mal receives the property, as an heir or because of no ecipient. Moreover, is a Muslim who leaves behind no heir, allowed to bequeath all his properties to whomever he wishes without obtaining a prior consent from the bayt al-mal? This article examines the entitlement of the bayt al-mal and the possibility of a Muslim to bequeath all his properties without the consent of the former.